Kryminały Stanisława Lema jako eksperymenty gatunkowe = Stanisław Lem`s "detective stories" as experimental literary genres - Dajnowski, Maciej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The plot of a detective story can be interpreted as a metonymy of a cognitive situation, a model ofcognition recognized in its general conditions. Due to this fact, novelists (especially those belonging tothe universe(s) of late modernism and postmodernism) often take advantage of this kind of plot andcreate novels-metaphorical treaties on human epistemological potential (or rather: the very lack of it).
Keywords: Lem, Stanisław (1921-2006); powieść kryminalna; literatura polska - 20 w. - tematyka